A conceptual model for energy management in the steel industry: A Soft System Methodology (SSM) approach - Muhammad Ibrahim Ats-Tsauri; Bagus Wilarnugroho; Humiras Hardi Purba (SINERGI, 2022)
This paper aims to use Soft Systems Methodology (SSM) to develop the steel industry's energy management framework. It proposes a soft system approach to analyze the complex situation of developing a support system for energy management. This approach consists of identifying the system scope, discovering underlying problems within, deriving a conceptual model from the complex situation, and identifying possible actors and activities to bring the conceptual model closer to reality. The identified activities could serve as a guideline for designing and developing an effective energy management framework in the steel industry. The result might also be further developed to drive the feasible, desirable changes into real implementation strategies and action plans. Currently, there is very limited SSM academic research in energy management. Hence the researchers sincerely hope that this study might help to drive the SSM methodology application in this field, in conjunction with the body of knowledge of Industrial and Systems Engineering (IISE).